Design and Evaluation of Submersible 11/0.415kV Distribution Substation for Flood Prone Areas - M. D. M. Amir; S. Ishak; A. Raj Gopal (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Flood levels exceeding 2 metres above ground level has been observed causing electrical equipment in the 11/0.415kV substation to be fully submerged. This caused widespread supply disruption as the equipment need to be switched off due to safety reasons and prevention of further equipment damage. The use of submersible equipment and accessories has been identified as one of the mitigation methods to ensure continuous electrical supply during flood events. A research project was undertaken to develop the design criteria of the selection of submersible equipment and accessories as well as to develop the test method and evaluate the selected submersible equipment and accessories in a substation configuration. All the equipment could continuously operate in ON condition during the wet test. However, design improvements are suggested for the submersible switchgear and feeder pillar for better performance during and after flood events.